Teaching data science to undergraduate translation trainees: Pilot evaluation of a task-based course - Yan, Da; Wang, Junyue (Frontiers in Psychology, 2022)
The advancement in technology has changed the workflow and the role of human translator in recent years. The impact from the trend of technology-mediated translation prompted the ratification of technology literacy as a major competence for modern translators. Consequently, teaching of translation technology including but not limited to Computer-aided Translation (CAT) and Machine Translation (MT) became part of comprehensive curricula for translation training programs. However, in many institutions, the teaching of translation technology was haunted by issues such as: narrow scope of curriculum design, outdated technologies, and unbalance between theories and practices in teaching. The study was the pilot evaluation of a tailored course to foster translation trainees’ knowledge and abilities of data science. The course was designed to be a fundamental step toward sophisticated translation technologies. During the pilot evaluation of the 8-week course, eighty-five students (n=85) were recruited as participants. The study adopted a mix-method design by employing a survey to investigate student’s level of satisfaction towards the course and focus group discussion to understand students’ attitudes and perceptions of key aspects of the course. By interpreting the results from statistical analysis of the survey (5.39/7) and thematic analysis of the focus group discussion, the course of data science for translators was well-received among participants. The evaluation project manifested the feasibility and effectiveness of a translator-oriented data science course.